Implementation Of The Second Re-Vote In Labuhan Batu In 2020 - Fauziah Nur Siregar; Hamdani Harahap; Hatta Ridho (PERSPEKTIF, 2023)
In light of the Re-Voting (PSU) process during the 2020 concurrent elections, this research sought to critically evaluate the performance of the KPPS Labuhanbatu Regency. Utilizing a qualitative case study methodology, a comprehensive dataset was compiled from in-depth interviews and meticulous document analysis, offering a holistic understanding of the intricacies and experiences associated with the event. The evaluation criteria were anchored on five pivotal indicators delineated by Kasmir, encompassing Quality, Quantity, Time, Cooperation Between Employees, and Supervision. Preliminary findings paint a picture of commendable dedication by the KPPS; however, their performance fell short of optimal standards. Beyond a mere assessment, this study carves out a roadmap, shedding light on the nuances of election management in Labuhanbatu Regency and pinpointing critical areas that demand attention and refinement to fortify future electoral endeavors.